IMPROVING THE TENTH GRADE STUDENTS’ SPEAKING SKILLS BY USING DISCOVERY LEARNING WITH ENGLISH SONGS AS MEDIA AT AL IHSAN SENIOR HIGH SCHOOL, TANJUNG LAGO - Desi Rosa Ria (Universitas PGRI Palembang, 2020)
The objective of the research was to know how the use of the discovery learning model with songs as media could improve the tenth-grade students’ speaking skills at Al Ihsan Senior High School, Tanjung Lago. The action research model employed Kemmis and McTaggart's. It consisted of four steps which were planning, action, observation, and reflection. The results of the research show that there was an improvement in the students’ speaking skills by implementing the discovery learning and English songs as media. The improvement was also supported by the percentage of students’ average scores. The percentage improvement in the average value of students from cycle1 and cycle2 is 2,46%, from cycle 2 and cycle 3 is 3,45 %. Then from the result of the test that the researcher got in the last cycle, there were 84% of students who got up to minimum criteria score.